2011
DOI: 10.2217/ijr.11.55
|View full text |Cite
|
Sign up to set email alerts
|

Single- versus dual-infusion of B-cell-depleting antibody ocrelizumab in rheumatoid arthritis: results from the Phase III FEATURE trial

Abstract: Patients & methods PatientsPatients (≥18 years of age) had active disease, defined as a diagnosis of RA using the 1987 American College of Rheumatology (ACR) criteria. The main inclusion criteria were: swollen joint count ≥4 (66-joint count) and tender joint count ≥4 (68-joint count) at screening and baseline; C-reactive protein ≥0.6 mg/dl or erythrocyte sedimentation rate ≥28 mm/h; and positivity for Aim: To test the hypothesis that a therapeutic dose of ocrelizumab (200 mg × 2), can be administered as a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…OCR500+MTX demonstrated clinical benefit by improving signs and symptoms of RA and radiographic outcomes [10][13]; however this dose was associated with an increased incidence of SIEs. OCR200+MTX did not show superior efficacy compared with existing therapies, but was safe and well-tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OCR500+MTX demonstrated clinical benefit by improving signs and symptoms of RA and radiographic outcomes [10][13]; however this dose was associated with an increased incidence of SIEs. OCR200+MTX did not show superior efficacy compared with existing therapies, but was safe and well-tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…The study designs and numbers of patients randomized were reported previously [10][13] and are summarized in Table 1. During the DBPC period of STAGE, SCRIPT and FILM, patients received treatment on Days 1 and 15 followed by a retreatment course at Weeks 24 and 26 (patients in FILM were eligible for 2 additional retreatment courses at Weeks 52 and 54, and Weeks 76 and 78).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of intravenous (IV) ocrelizumab for the treatment of RA was studied in four phase III, international, randomized, double-blind, placebo-controlled trials: SCRIPT, STAGE, FILM, and FEATURE. STAGE [ 9 ], FILM [ 10 ], and FEATURE [ 11 ] studied ocrelizumab in RA patients on stable MTX who had inadequate responses to MTX, while SCRIPT [ 12 ] studied ocrelizumab in RA patients taking MTX or leflunomide who had inadequate responses to at least one TNF antagonist. Patients in the STAGE, FILM, and SCRIPT studies continued taking their stable doses of MTX or leflunomide and were assigned to receive ocrelizumab at 200 mg × 2, 500 mg × 2, or placebo × 2 at baseline and at week 24.…”
Section: Anti-cd20 Mabs In Rheumatoid Arthritismentioning
confidence: 99%